1994
DOI: 10.1016/0014-5793(94)00379-3
|View full text |Cite
|
Sign up to set email alerts
|

Antipeptide antibodies directed against the C‐terminus of protein kinase Cζ (PKCζ) react with a Ca2+‐ and TPA‐sensitive PKC in HT‐29 human intestinal epithelial cells

Abstract: We have studied the PKC isoforms present in HT-29 M6 colon cancer cells, the differentiation of which to mucus-secreting cells is blocked by TPA. In addition to a major 72 kDa band, a 77 kDa PKC isoform was recognized by two different antibodies raised against a C-terminus-specific peptide for the TPA-insensitive isoform, PKCC. By different criteria (association to the membrane, down-regulation, PKC activity in immunoprecipitates) we conclude that, contrary to the 72 kDa band, the 77 kDa band corresponds to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…The highest molecular weight band (C, 80 kD) seen on this blot may represent a conventional isozyme, possibly PKC-ex; cross-reactivity of C-terminal C antibodies with conventional isozymes has been reported previously. (30,31) As was observed with the PKC-exspecific antibody (Fig. lA), this isozyme was expressed in each of the osteoblasts screened.…”
Section: Pkc Isozyme Expression In Normal Osteoblasts and Osteoblastisupporting
confidence: 62%
“…The highest molecular weight band (C, 80 kD) seen on this blot may represent a conventional isozyme, possibly PKC-ex; cross-reactivity of C-terminal C antibodies with conventional isozymes has been reported previously. (30,31) As was observed with the PKC-exspecific antibody (Fig. lA), this isozyme was expressed in each of the osteoblasts screened.…”
Section: Pkc Isozyme Expression In Normal Osteoblasts and Osteoblastisupporting
confidence: 62%
“…The third antibody (Upstate Biotechnology) used in the present study is reported not to cross-react with either PKC-␣, PKC-, or PKC-(according to information provided by the manufacturer). It has also been reported that antibodies directed against the COOH terminus of PKC-react with a Ca 2ϩ and phorbol ester-sensitive PKC isoform (25). However, the kinase that is the subject of this report is only weakly activated by a combination of PMA, Ca 2ϩ , and PS and has sustained activity in the absence of exogenous lipids.…”
Section: Fig 6 Abrogation Of Lps-induced Activation Of Pkc-by the Pmentioning
confidence: 44%
“…in subsequent immunoblots using PKC £ and PKC e antibodies, since the other apparently specific signals of 82 kDa and 80 kDa represent conventional PKC protein (29,30) and PKC 8 (C.S.-P, C.L.B., T.J.B., unpublished observations), respectively. Other PKC isozymes were not quantified: PKC P immunoreactivity was extremely low (not shown), using any of three PKC 3-specific antibodies, making densitometry impracticable, while PKC 7, PKC r\, and PKC 1 are absent or only poorly expressed in skeletal muscle (24,31,32).…”
Section: Resultsmentioning
confidence: 97%